Accretion processes in astrophysics XXI Canary Islands Winter School of Astrophysics - Casares Velázquez, Jorge 1964-; González Martínez-País, Ignacio 1959-; Shahbaz, Tariq 1970- (Cambridge University Press, 2014)
It has been more than fifty years since the first significant paper on accretion flows was written. In recent years, X-ray satellites capable of identifying accretion disks and radiation jets - indications that accretion has taken place - have significantly advanced our understanding of these phenomena. This volume presents a comprehensive and up-to-date introduction to the major theoretical and observational topics associated with accretion processes in astrophysics. Comprising lectures presented at the twenty-first Winter School of the Canary Islands Institute of Astrophysics, the text emphasises the physical aspects of accretion, investigating how radiation jets are produced, how accretion power is divided between jets and radiated energy, the geometry of accretion flow, and the accretion processes of active galactic nuclei. Written by an international team of experienced scientists, chapters offer young researchers key analytical tools for supporting and carrying out the next generation of front-line research.